Stephanitis pyrioides (Scott) (Heteroptera Tingidae): a lace bug new to Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Stephanitis pyrioides (Scott) is recorded for the first time from Italy (Tuscany). Adults were found attacking plants of Rhododendron spp. (azaleas and rhododendrons) in Lucca at the Botanical Gardens in the autumn 2004. The winter was passed in the egg stage. Details on the morphology of the species are given in order to separate it from other congeneric species present in Italy: S. pyri F. and S. takeyai Drake & Maa. Remarks are made on its taxonomy, geographical distribution, host plants, life cycle and damage.
Keywords: Tingidae; Stephanitis; Azalea lace bug; Rhododendron spp.